In bird flu fight, 'Sentinel' chicks play key role get sick - Orejas, Tonette T. (2017)
Day-old chicks serve as indicators of whether bird flu still stalks the town of San Luis, Pampanga province or had been stamped out.
Keywords: Avian Influenza A virus -- Pampanga; Piñol, Manny